Effect of Continuous and Sequential Therapy among Veterans Receiving Daptomycin or Linezolid for Vancomycin-Resistant Enterococcus faecium Bacteremia - Britt, Nicholas S. (Antimicrob Agents Chemother, 2017)
Vancomycin-resistant Enterococcus faecium bloodstream infections (VREF-BSI) cause significant mortality, highlighting the need to optimize their treatment. We compared the effectiveness and safety of daptomycin (DAP) and linezolid (LZD) as continuous or sequential therapy for VREF-BSI in a national, retrospective, propensity score (PS)-matched cohort study of hospitalized Veterans Affairs patients (2004 to 2014). We compared clinical outcomes and adverse events among patients treated with continuous LZD, continuous DAP, or sequential LZD followed by DAP (LZD-to-DAP). Secondarily, we analyzed the impact of infectious diseases (ID) consultation and source of VREF-BSI. A total of 2,630 patients were included in the effectiveness analysis (LZD [n = 1,348], DAP [n = 1,055], LZD-to-DAP [n = 227]). LZD was associated with increased 30-day mortality versus DAP (risk ratio [RR], 1.11; 95% confidence interval [CI], 1.01 to 1.22; P = 0.042). After PS matching, this relationship persisted (RR, 1.13; 95% CI, 1.02 to 1.26; P = 0.015). LZD-to-DAP switchers had lower mortality than those remaining on LZD (RR, 1.29; 95% CI, 1.03 to 1.63; P = 0.021), suggesting a benefit may still be derived with sequential therapy. LZD-treated patients experienced more adverse events, including a ≥50% reduction in platelets (RR, 1.07; 95% CI, 1.03 to 1.11; P = 0.001). DAP was associated with lower mortality than was LZD in patients with endocarditis (RR, 1.20; 95% CI, 1.02 to 1.41; P = 0.024); however, there was no statistically significant association between treatment group and mortality with regard to other sources of infection. Therefore, source of infection appears to be important in selection of patients most likely to benefit from DAP over LZD.